Zakat Produktif Untuk Meningkatkan Kinerja Produksi, Motivasi dan Religiusitas Mustahiq (Studi Kasus Pada BAZ Jatim) - Nidityo, Herwindo Ghora; Laila, Nisful (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research aims to determine the role of productive zakat toward the productive performance of mustahiq at their workplace.This research used qualitative methods through descriptive case study analysis.Characteristic of theinformant research are the mustahiq that already registered as BAZ Jatim member. The number of informant tested of this research by six mustahiq and there are two managers of BAZNAS were asked for further information from the beginning of the research. The sampling technique used by this research is interview instrument and triangulatin process as the validity tool.Based on the results of the research indicate that there are several role of productive zakat that affect the productive performance of mustahiq compared to the period before the zakat was distributed. The four factors as a result are the three main indicators, which is quantitative indicators, are change of number from the raw materials, quantity of productions, and the frequency of productions done. And the additional indicator is the effectivity of resource used, which is the factory overhead used of the production. Furthermore, in the process of research the productive zakat is also have a role to increasethe motivation to produce and the religiosity of mustahiq.Advice for the distributioninstitutions of zakat, are improves the number of productive programs and increases the management and distributions of the zakat, infaq, and shadaqah as a funding for the empowerment the people so that of the lng term the zakat can be an instrument for the poor and slum reduction. For the second next research, are adding the informations of productive zakat and its management.